Strategy to Increase Public Participation in Monitoring General Elections in Papua - Rusdiansyah (Generasi Sains Indonesia, 2024)
In this research, the approaches to enhance the public engagement in the monitoring of general elections in Papua, Indonesia a politically sensitive area with restricted freedom are explored. Employing both structured and unstructured research methodologies, the study identifies and examines the politics of exclusion, including political violence, distrust of the electoral process, and geographic constraints, as the chief causes of non-attendance at elections among citizens. As it can be seen from the above analysis, political victimisation, especially from political big-wigs and relevant local offices, appears to predominate as a barrier to stakeholder engagement. As the way forward for all these challenges, the study proposed an increase in the protection of whistle blowers, utilizing online means for remote monitoring of electoral activity, and CSO’s strengthening to improve electoral inclusiveness. Overall, the study accrues important findings on the ways that legal, technological, and community driven approaches advance democratic accountability as well as seek to achieve a more transparent electoral process in Papua.